HIV-1 seronegativity in a child with proved perinatal HIV infection on HAART. Issue 5 (30th September 2005) - Desai, N; Mathur, M; Abu-Lawi, K
Abstract : Objectives: To report the unexpected absence of HIV-1 antibodies and provirus in the peripheral blood of a 4 year old with previously diagnosed perinatal HIV infection. Methods: Case study including review of clinic and laboratory records and confirmation of results of HIV-1 enzyme linked immunosorbent assay (ELISA), western blot, and HIV-1 DNA PCR from reference laboratory. Results: This child had high plasma viral load at the initiation of highly active antiretroviral therapy (HAART) at 10 months of age. Following undetectable HIV viraemia continuously for a 3 year period, he had normal CD4 and immunoglobulin levels. When retested at the request of the parent, HIV-1 ELISA, western blot, and HIV DNA PCR were all negative, raising the question of misdiagnosis and the parental misperception of a "cure." A rebound increase in viral load on cessation of therapy led to these diagnostic tests becoming positive again, with better parental acceptance of the diagnosis and treatment plan. Conclusions: Patients and providers should exercise caution in interpreting negative serological tests in children on HAART.